Exploring the unusual: a testosterone-secreting ovarian tumor - Kaur, Harpreet; Singh, Neha; Bharti, Sushma; Kaur, Gurwinder (Autopsy and Case Reports, 2024)
Ovarian steroid cell tumors are rare, representing less than 0.1% of all ovarian neoplasms. Among the myriad causes of hirsutism, ovarian tumors account for 1% of the reported cases. We present the case of a 49-year-old parous postmenopausal woman who sought medical attention for hirsutism for 2 years. This case illustrates the unusual and interesting connection between rare ovarian pathology and the clinical manifestation of hirsutism in a postmenopausal patient. Her ultrasonography and MRI showed a right adnexal mass of solid-cystic consistency with thin septations. Her laboratory workup revealed high levels of total testosterone of 256 ng/ml (8.4-48.1ng/ml) and free testosterone of 7.36 pg/ml (0.2-4.1 pg/ml), while DHEAS - 234 µg/dl (35.4-256 µg/dl) and CA125 - 15.8U/L (0.0-35 U/L) were in the normal range. She underwent exploratory laparotomy with a total abdominal hysterectomy and oophorectomy. Histopathological examination and immunohistochemistry conclusively established the presence of a steroid cell tumor, specifically classified as "Not Otherwise Specified"(NOS), in the right ovary.